2013
DOI: 10.1016/j.jdent.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action studies of a new desensitizing mouthwash containing 0.8% arginine, PVM/MA copolymer, pyrophosphates, and 0.05% sodium fluoride

Abstract: The studies presented in this paper support occlusion of the dentine surface upon the deposition of an arginine-rich layer together with copolymer and phosphate ions from an alcohol-free mouthwash containing 0.8% arginine, PVM/MA copolymer, pyrophosphates and 0.05% sodium fluoride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…For the purposes of evaluating this new desensitizing formulation, the Investigators used a dentine disc methodology to determine the effectiveness of a number of commercially available oral rinses in reducing fluid flow through tubular occlusion. The zinc substituted HA was included to compare the effectiveness of a commercially available oral rinse: both the arginine and PVM/MA copolymer and 1.4% potassium oxalate oral rinses have been reported to be effective in reducing DH and were used as positive controls [10, 11, 13, 14] and the potassium nitrate oral rinse was included as a negative control as its mode of action is generally considered to be by nerve desensitization rather than by tubular occlusion. In order to test the potential ability of a desensitizing product prior to clinical evaluation, in vitro and/or in situ studies are often conducted in order to determine a possible mode of action of the product.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of evaluating this new desensitizing formulation, the Investigators used a dentine disc methodology to determine the effectiveness of a number of commercially available oral rinses in reducing fluid flow through tubular occlusion. The zinc substituted HA was included to compare the effectiveness of a commercially available oral rinse: both the arginine and PVM/MA copolymer and 1.4% potassium oxalate oral rinses have been reported to be effective in reducing DH and were used as positive controls [10, 11, 13, 14] and the potassium nitrate oral rinse was included as a negative control as its mode of action is generally considered to be by nerve desensitization rather than by tubular occlusion. In order to test the potential ability of a desensitizing product prior to clinical evaluation, in vitro and/or in situ studies are often conducted in order to determine a possible mode of action of the product.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of the tooth protective effect of arginine‐containing products has been proposed for many years. Many clinical studies have shown that Pro‐Argin toothpaste (8% arginine, calcium carbonate and 1450 ppm fluoride, Colgate‐Palmolive Company, USA) or Pro‐Argin mouthwash (0.8% arginine, PVM/MA copolymer, pyrophosphates, and 0.05% sodium fluoride) can effectively treat dentine hypersensitivity by blocking the dentinal tubules . It has been suggested that the positively charged guanidinium group of arginine interacts with the negatively charged groups on dentine surface such as fluoride ions, promoting the deposition of calcium and phosphorus in the dentinal tubules from saliva, thereby occluding dentine tubules and reducing fluid flow .…”
Section: Introductionmentioning
confidence: 99%
“…Para el efecto se han utilizado diversos métodos que permiten aplicar dispositivos útiles para la medición de la permeabilidad de la dentina, así como el análisis bajo microscopía para la visualización de la oclusión de los túbulos dentinarios. Este último es importante, ya que los túbulos dentinarios establecen el 86% de la resistencia al flujo de líquido en el interior de los mismos; por lo tanto, sí existe una reducción en el diámetro del túbulo se reduce el flujo de líquido, y por ende promueve el alivio a la sensibilidad de la dentina [26][27][28].…”
Section: Análisis De Diámetro De Túbulos Dentinariosunclassified